Mechanics of Machines - Ramamurti, V. (Viswanatha), 1938-, author 349271 (Oxford, UK : Alpha Science)
While emphasising the industrial relevance of the mechanics of machines, this book dispenses with conventional inaccurate graphical methods and presents general vector approaches for both plane and space dynamic problems.